Profil dermatitis seboroik pada pasien di Poliklinik Rawat Jalan Kulit dan Kelamin RSUD Wangaya Denpasar periode Oktober 2017-Oktober 2018 - Elisia Elisia; Tjokorda Dalem Pemayun (Intisari Sains Medis, 2019)
Introduction: Seborrheic dermatitis is a chronic superficial skin disorder occurs in 2-5% of population with the symptom of erythematous plaque with slightly yellowish scaling and without clear border, it caused by multifactorial etiopathogenesis includes sebaceous gland secretion, Malassezia fungi colonization, and immune response. This disease is higher in rich sebaceous gland area, is mostly found in the face, upper trunk, and intertriginous (inguinal, inframammary, and axilla).Aim: This study aimed to know the profile of seborrheic dermatitis patients in dermatovenereology outpatient clinic of Wangaya General Hospital in October 2017-October 2018 period.Methods: This study is a retrospective study based on the number of cases, sex, age group, location of lesion, and type of treatment from patient medical records of dermatovenereology outpatient clinic in Wangaya General Hospital in 2017-2018 period.Results: Seborrheic dermatitis mostly found in men (64,2%) with the adult age group is the highest number (77,6%). This disease often affected the face area in 36 patients (53,7%). The most frequent treatment used was anti-inflammation agent in 41 samples (61,2%). In this study, anti-inflammation used were topical corticosteroids (64,2%), there were betamethasone for adults and hydrocortisone for children.Conclusion: Seborrheic dermatitis were mostly found in male, occurred in the age group â‰¥35 years. The location of lesion is higher found in face area and mostly treated with corticosteroidÂ